Development of Mobile Learning Applications for Android Based on Artificial Intelligence - Tatik Mariyanti (Pandawan Sejahtera Indonesia, 2023)
In order to enable students to study autonomously and without being constrained by time and distance, this research was done to design an M-Learning learning media based on learning media on artificial intelligence. constrained by time and space, as well as to boost students' enthusiasm for studying. The following are the problems that need to be solved by this research: (1) How feasible is an android-based M-learning application for the field of artificial intelligence? (2) What are the students' reactions to the M-learning application built for Android in the Artificial Intelligence course?Research and development, sometimes known as R&D, is the research methodology employed. Students in the informatics engineering department at Raharja University served as the study's research targets. Techniques Instrument reliability and validity assessments as well as questionnaires are employed as data gathering methods respondents. Then, the examination of media viability and student reaction is performed as a data analysis approach. Descriptive analysis was done on the student replies. (1) Media validation by professional validators is calculated at 92.5% by percentage, according to the results. On the basis of this, it can be said that the android-based M-learning application falls within the category of